Phase engineering of H/T-Nb2O5 homojunction for enhanced lithium-ion storage - Sheng Li; Jun Li; Wenjie Zhang; Sherif A. El‐Khodary; Yubo Luo; Dickon H.L. Ng; Xiaoshui Peng; Jiabiao Lian (ChemPhysMater)
Phase engineering has gained significant attention in energy-storage applications due to its ability to tailor the physicochemical properties and functionalities of electrode materials. In this study, we demonstrate the in-situ partial phase conversion of niobium pentoxide (Nb2O5), resulting in the formation of a monoclinic/orthorhombic (H/T-Nb2O5) heterophase homojunction. This study further confirms that the unique heterophase interface plays a crucial role in regulating the local electronic environment, resulting in charge redistribution, the formation of an internal electric field, and enhanced electron transfer. Moreover, the presence of abundant phase interfaces offers additional reactive sites for Li+ ion adsorption, thereby enhancing reaction dynamics. The synergistic effects within the H/T-Nb2O5 homojunction are reflected in its high Li+ storage capacity (413 mAh g−1 at 100 mA g−1), superior rate capability, and cycling stability. Thus, this study demonstrates that the construction of heterophase homojunctions offers a promising strategy for developing high-performance anode materials for efficient Li-ion storage.